Detection of black bean lines with adaptation in the humid tropics of southern Mexico - Tosquy-Valle, Oscar Hugo; López-Salinas Ernesto; Acosta-Gallegos, Jorge Alberto; Villar-Sánchez Bernardo (Revista Mexicana de Ciencias Agrícolas, 2018)
In the Bean Improvement Program of the Experimental Station from INIFAP in Cotaxtla, the breeding method by introduction has been effective generating varieties for the humid tropics of southern Mexico. From 2007 to 2010, a trial was conducted in four environments from Veracruz and one in Chiapas, in order to determine the adaptation of 14 black bean lines from the Escuela Agricola Panamericana de Zamorano and the University of Puerto Rico, along with varieties Black Tacana and Black Jamapa as control, to identify lines with highest yielding and widely adapted to this region. The trial was conducted in a randomized block design with three replications. It was recorded genotype reaction to diseases that are present naturally on the environment: angular leaf spot and bean golden yellow mosaic virus, plant mortality was recorded by the incidence of systemic necrosis and grain yield was determined. Five lines were located in the outstanding yield group (p≤ 0.05), which were stable in their behavior (bi= 1 and S2di = 0) and showed adaptability to environmental conditions in which beans are produced in the humid tropics of Veracruz and Chiapas. The X02-33-147-2 line was the most productive with 1 400.4 kg ha-1; which average yield was significantly higher than Black Tacana and Black Jamapa (regional controls). The same line also showed resistance to angular leaf spot and tolerance to bean golden yellow mosaic virus.